Humanoid Robot Balance Control Using the Spherical Inverted Pendulum Mode - Elhasairi, Ahmed; Pechev, Alexandre (Frontiers in Robotics and AI, 2015)
Human beings are highly efficient in maintaining standing balance under the influence of different perturbations. However, biped humanoid robots are far from exhibiting similar skills. This is mainly due to the limitations in the current control and modelling techniques used in humanoid robots. Even though approaches using the Linear Inverted Pendulum Model and the Preview Control schemes have shown improved results, they still suffer from shortcomings in the overall generated motion. We propose here a model and control approach that aims to overcome the limiting assumptions in the LIPM models, through using the ankle joint variables in modelling and control of the standing balance of the humanoid robot.